1987
DOI: 10.1083/jcb.105.1.41
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of confocal versus conventional imaging of biological structures by fluorescence light microscopy.

Abstract: Abstract. Scanning confocal microscopes offer improved rejection of out-of-focus noise and greater resolution than conventional imaging. In such a microscope, the imaging and condenser lenses are identical and confocal. These two lenses are replaced by a single lens when epi-illumination is used, making confocal imaging particularly applicable to incident light microscopy. We describe the results we have obtained with a confocal system in which scanning is performed by moving the light beam, rather than the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
356
1
2

Year Published

1990
1990
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 793 publications
(361 citation statements)
references
References 19 publications
2
356
1
2
Order By: Relevance
“…The emission filter was a highpass from 550 nm. We used full excitation power and, in agreement with White et al (66) who used comparable settings, we found no degradation of the image quality due to fluorescence saturation.…”
Section: Methodssupporting
confidence: 85%
“…The emission filter was a highpass from 550 nm. We used full excitation power and, in agreement with White et al (66) who used comparable settings, we found no degradation of the image quality due to fluorescence saturation.…”
Section: Methodssupporting
confidence: 85%
“…Recent developments in fluorescence microscopy (e.g., White et al, 1987) and vital staining of intracellular membranes with carbocyanine dyes (Terasaki et al, 1984;Terasaki, 1989; have made it possible to follow ER dynamics in living cells (Terasaki et al, 1984(Terasaki et al, , 1986Allan and Brown, 1988;Kachar and Reese, 1988;Terasaki, 1989Terasaki, , 1990Knebel et al, 1990;McCauley and Hepler, 1990). We have developed a technique based on the spreading of dye molecules through the membranes of the ER after microinjection of an oil droplet saturated with dye (Terasaki and Jaffe, 1991).…”
mentioning
confidence: 99%
“…Using a pinhole to reject out-of-focus light, the optical sectioning capability and hence axial resolution was dramatically improved over standard widefield microscopes (White et al 1987). Theoretically, a small pinhole also increases lateral resolution up to a factor of 1.4.…”
Section: Developments Toward Extended Resolutionmentioning
confidence: 80%